Teknologi Komputer dan Proses Kreatif Musik Menuju Revitalisasi Pembelajaran Seni Musik - Wahyu Widodo, Tri (Institut Seni Indonesia Yogyakarta, 2013)
The impact of computer technology advancement in current music education, as well as musical life in general, is undoubted cannot be avoided. Modern music software has given a great contribution to musical creativity so that computer technology can help tertiary music education process to be much better.Keywords: Computer technology, music education, musical creativity